Cloning of acetyl CoA carboxylase cDNA and the effects of spirodiclofen on the expression of acetyl CoA carboxylase mRNA in Panonychus citri. Issue 1 (27th May 2015) - Yu, Shijiang; Tian, Huixia; Yang, Juan; Ding, Lili; Chen, Fei; Li, Xiaojiao; Yue, Jiansu; Liu, Haoqiang; Ran, Chun
Abstract The citrus red mite, Panonychus citri (McGregor) (Acari: Tetranychidae), is an important pest worldwide. Previous studies showed that acetyl CoA carboxylase (ACCase) may be a critical target of spirodiclofen, a recently introduced insecticide. Therefore, we cloned the PcACCase gene and obtained a full‐length cDNA (Genbank accession number KJ675439). The open reading frame was 6 972 bp, coding for 2 323 amino acids. The PcACCase protein had a theoretical molecular weight of 262.82 kDa and an isoelectric point of 6.31, and it contained six conserved domains and one low‐complexity region. Quantitative real‐time PCR showed that spirodiclofen can up‐regulate the expression levels of ACCase mRNA during all four developmental stages.